Tiller's Guide to Indian Country : Economic Profiles of American Indian Reservations, Third Edition. - Tiller, Veronica E. Velarde (Book collections on Project MUSE., 2015)
Tiller's Guide to Indian Country tells the collective story of the little-known economic success attained by tribal enterprises owned by the 568 Indian tribes and Alaskan Native villages in thirty-three states. It has been recognized since 1996 as the ultimate resource on contemporary tribal economies and has become indispensable to government entities, businesses working with the tribes, libraries, and scholars. This reference edition profiles each tribe's history and culture, with detailed information about their communities, natural resources, enterprises, and environmental concerns, as well as their contact information. It also features profiles on leading tribal enterprises, businesses doing business with tribes, and nonprofit organizations that have made significant contributions to economic development in Indian Country.